2007
DOI: 10.1152/physiolgenomics.00013.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differences in postingestive metabolism of glutamate and glycine between C57BL/6ByJ and 129P3/J mice

Abstract: Amino acids are essential nutrients for living organisms. There are genetic differences in voluntary consumption of amino acids among mouse strains. In two-bottle preference tests, C57BL/6ByJ (B6) mice consume more glutamate (Glu) and glycine (Gly) solutions than do 129P3/J (129) mice. To examine the role of postingestive metabolism of these amino acids in regulation of their intake, we compared metabolism of orally administered Glu and Gly in B6 and 129 mice. After administration of Glu, there were increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…This conclusion is entirely consistent with two other lines of evidence: strain-specific effects of prior experience with MSG on its intake [21], and strain differences in the metabolism of orally administered MSG [38]. In the latter study [38], we found that after intragastric administration of MSG B6 mice preferentially metabolize it through gluconeogenesis, whereas the predominant process for 129 mice is thermogenesis. This suggests that a process related to gluconeogenesis of the ingested glutamate generates a rewarding stimulus, and that the glutamate-induced post-ingestive thermogenesis generates an aversive stimulus.…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion is entirely consistent with two other lines of evidence: strain-specific effects of prior experience with MSG on its intake [21], and strain differences in the metabolism of orally administered MSG [38]. In the latter study [38], we found that after intragastric administration of MSG B6 mice preferentially metabolize it through gluconeogenesis, whereas the predominant process for 129 mice is thermogenesis. This suggests that a process related to gluconeogenesis of the ingested glutamate generates a rewarding stimulus, and that the glutamate-induced post-ingestive thermogenesis generates an aversive stimulus.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly important is the fact that dietary amino acids and sugars differentially control the relative amounts of insulin and glucagon to be secreted by the pancreas (Young, 2005;Ji and Bachmanov, 2007), an effect that will directly influence the organism's ability to mobilize stored fuels (Ferrer et al, 2003;Buch et al, 2008). This suggests that appetites for these macronutrients might be under the control of metabolic needs in addition to taste quality, as evidenced by increased intake levels of essential amino acids that had been withdrawn from an animal's diet (Markison et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The release of urea from the urea‐containing Fmoc‐FuF gel was evaluated next. To this end, gels were immersed in water for a period of 6 days, during which the release of urea into the aqueous environment was monitored daily by a colorimetric assay . The concentration of released urea increased gradually over time, from 4% (day 1) to 91% (day 6) of its initial concentration in the gel (Figure j).…”
mentioning
confidence: 99%